2011
DOI: 10.1199/tab.0146
|View full text |Cite
|
Sign up to set email alerts
|

The Functions of RNA-Dependent RNA Polymerases in Arabidopsis

Abstract: One recently identified mechanism that regulates mRNA abundance is RNA silencing, and pioneering work in Arabidopsis thaliana and other genetic model organisms helped define this process. RNA silencing pathways are triggered by either self-complementary fold-back structures or the production of double-stranded RNA (dsRNA) that gives rise to small RNAs (smRNAs) known as microRNAs (miRNAs) or small-interfering RNAs (siRNAs). These smRNAs direct sequence-specific regulation of various gene transcripts, repetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 194 publications
3
130
0
1
Order By: Relevance
“…Interestingly, we found significant correlations between RNA structure hot spots and genomic sites of siRNA-mediated, heterochromatic histone modifications and DNA methylation ( Figure 2E; see Supplemental Figure 2 online), providing experimental support for the importance of RNA secondary structure in epigenetic regulatory pathways. Additionally, it is well accepted that DCL1 recognizes structured regions of RNA molecules for production of smRNAs (Voinnet, 2009;Willmann et al, 2011), and our transcriptome-wide structural studies also support this model of substrate recognition for other DCL proteins (e.g., DCL3) in Arabidopsis (see Supplemental Figure 2 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, we found significant correlations between RNA structure hot spots and genomic sites of siRNA-mediated, heterochromatic histone modifications and DNA methylation ( Figure 2E; see Supplemental Figure 2 online), providing experimental support for the importance of RNA secondary structure in epigenetic regulatory pathways. Additionally, it is well accepted that DCL1 recognizes structured regions of RNA molecules for production of smRNAs (Voinnet, 2009;Willmann et al, 2011), and our transcriptome-wide structural studies also support this model of substrate recognition for other DCL proteins (e.g., DCL3) in Arabidopsis (see Supplemental Figure 2 …”
Section: Discussionsupporting
confidence: 76%
“…As expected, transposable elements were found to be a rich source of structure hot spots ( Figure 2A). This is not surprising because transcriptional silencing of these regions is likely mediated by small silencing RNAs that require a self-complementary fold-back structure and/or dsRNA intermediate for their biogenesis (Willmann et al, 2011). In support of this hypothesis, we found that duplex (dsRNA molecules arising from both strands) and nonduplex (i.e., secondary structure of an RNA molecule) structure hot spots are equally likely to arise from transposable elements (see Supplemental Figures 2A and 2B online).…”
Section: Identification and Characterization Of Structure Hot Spots Amentioning
confidence: 99%
“…Small interfering RNAs (siRNAs) are defined by the dependency of their biogenesis on an RNA-dependent RNA polymerase (RDR). The activity of at least three of the six RDRs (RDR1/2/6) encoded in the Arabidopsis thaliana genome is believed to generate a double-stranded RNA (dsRNA) intermediary that is recognized and cleaved by a Dicer enzyme to generate different classes of siRNAs; so far, little is known about the function of the triplicated paralogs RDR3/4/5 (Willmann et al, 2011). hc-siRNAs are ;24 nucleotides in length, generated from DCL3 activity from intergenic or repetitive regions of genome via the activity of the plant-specific RNA polymerases Pol IV and possibly Pol V (Matzke et al, 2009;Law and Jacobsen, 2010;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the new dsRNAs are cleaved by different DCLs, producing secondary siRNAs that are able to move systemically and amplify the silencing signal (for reviews, see Voinnet, 2008;Bologna and Voinnet, 2014). In Arabidopsis thaliana, six different RDRs have already been identified (RDR1-RDR6) (reviewed in Willmann et al, 2011). RDR1 and RDR6 are the two main antiviral RDRs (Wang et al, 2010).…”
Section: Rna Interference-mediated Resistancementioning
confidence: 99%